Oral supplementation with propionate is reflected in the serum of healthy individuals - Maximilian Schröder; Arijan Pasic; Frank Hirche; Svitlana Rozanova; Melissa Sgodzai; Barbara Gisevius; Lea Horstkemper; Ralf Gold; Katrin Marcus; Kalliopi Pitarokoili; Jeremias Motte; Katalin Barkovits; et al. (Therapeutic Advances in Neurological Disorders)
Background: Short-chain fatty acids (SCFAs), including propionic acid (PA), are key in immunological research. Supplementing PA has shown benefits for autoimmune diseases. A comprehensive understanding of the PA pharmacokinetics is essential for the optimal design and execution of studies utilizing orally administered PA. Objective: We propose two methods of measuring PA in serum, carried out by different laboratories. Design: Blood samples from 20 volunteers were collected hourly following PA supplementation. Methods: Serum propionate quantification was performed with two independent mass spectrometry-based (MS) analyses, including liquid-chromatography (LC)-MS and direct-infusion (DI)-MS. Results: PA levels increased within 1 h of ingestion of 500 mg PA. Serum concentrations ranged from 1.3 to 4.5 µmol/L, rising significantly after 1 h ( p  < 0.05). Serum levels returned to baseline within 2 h. No significant differences were found regarding sex or diet. Conclusion: The shown pharmacokinetics can be used in future PA research.